Pulmonary alveolar microlithiasis. - Onadeko, B. O. (BMJ Group, 1977)
A case of pulmonary avleolar microlithiasis is reported. This is of especial interest as it is the first case to be reported from Africa South of the Sahara. The clinical presentation of the patient follows a similar pattern as that of cases already described by other workers. The diagnosis in this case was made in life by a combination of radiological examination and a lung biopsy. The clinical presentat on and aetiology of the condition are briefly discussed.